2005
DOI: 10.2174/1568016053544363
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type I Receptor Blocker and Endothelial Function in Humans: Role of Nitric Oxide and Oxidative Stress

Abstract: Recent large clinical trials have shown that angiotensin II type I receptor blockers (ARBs) reduce cardiovascular morbidity and mortality in patients with heart failure, acute myocardial infarction, and hypertension. However, the mechanism underlying antiatherogenic effects of ARBs remains unclear. The vascular endothelium is involved in the release of various vasodilators, including nitric oxide (NO), prostacyclin, and endothelium-derived hyperpolarizing factor as well as vasoconstrictors. NO plays an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 137 publications
(275 reference statements)
3
19
0
1
Order By: Relevance
“…It is well known that NAPDH oxidase is composed of cytosolic components, such as p47phox, p67phox, and RC1, and membrane-spanning components, such as p22phox and gp91phox. Angiotensin II -induced NADPH oxidase activation is one of the major sources of ROS in the pathophysiologic mechanism of atherosclerosis (35,36). These observations are consistent with the findings of the present study, in which angiotensin II induced the expression of p47phox and production of the O 2 À radical.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is well known that NAPDH oxidase is composed of cytosolic components, such as p47phox, p67phox, and RC1, and membrane-spanning components, such as p22phox and gp91phox. Angiotensin II -induced NADPH oxidase activation is one of the major sources of ROS in the pathophysiologic mechanism of atherosclerosis (35,36). These observations are consistent with the findings of the present study, in which angiotensin II induced the expression of p47phox and production of the O 2 À radical.…”
Section: Discussionsupporting
confidence: 93%
“…5. Higashi et al confirmed that NADPH oxidase is the most important source of ROS in the vasculature (35). It is well known that NAPDH oxidase is composed of cytosolic components, such as p47phox, p67phox, and RC1, and membrane-spanning components, such as p22phox and gp91phox.…”
Section: Discussionmentioning
confidence: 99%
“…Modrick et al (2009) showed that in the absence of AT1, endothelial dysfunction did not occur in old mice, suggesting a novel and fundamental role for Ang II in age-related vascular dysfunction. While it is well established that Ang II produces oxidative stress in various tissues (Higashi et al 2005;Lassegue et al 2001;Seshiah et al 2002), the relative importance of Ang II and its ability to induce signaling that leads to vascular dysfunction with aging has been less well explored.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous reports showing the positive effect of blocking the converting enzyme or the AT1R on endothelial function. 38 ROS have a key role in the signaling pathways activated by angiotensin II in vascular cells. Therefore, we tested the involvement of ROS in LF remodeling.…”
Section: Discussionmentioning
confidence: 99%